Technical and Economic Valuation of Healthcare Building Upgrade - Berto, Raul.; Rosato, Paolo; Stival, Carlo Antonio; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
The book presents a methodology for detecting intervention needs on existing healthcare buildings and estimating the related costs, to perform a sustainable financial planning for modernization, regulatory adjustment and performance upgrade. By the identification of specific parameters, characterizing the building in terms of layout typology, technical features and services provision, it proposes a framework for the collection of relevant information to current regulations and standards. Integrated evaluation tools are developed to perform first a technical assessment of the investigated building, basing on the survey of its key features and on the codification of standard actions. Then, appraisal procedure valuates intervention cost from the similarity degree between the object of analysis and a set of interventions already performed on healthcare assets. The book offers a valuable tool for technical professionals, public administrations and healthcare managers engaged in maintenance and performance assessment of healthcare facilities.
Introduction -- Quick Requirement Assessment of Healthcare Buildings -- The Valuation of Upgrade Costs on Healthcare Buildings -- Data Management for Cost Valuation -- An Experimental Application of the Procedure -- Concluding Remarks.
Keywords: Facility management; Urban economics; Medical care; Facility Management; Urban Economics; Health Care; Health Facilities -- Design and construction; Health facilities -- Remodeling